Perancangan Sistem Pendataan Santri Dan Pendataan Hafalan Berbasis Android Di Ma’had Tahfizhul Qur’an Ahlus Shuffah - Karyawati, Endang (Jurnal Informatika dan Komputer, 2024)
This research aims to further analyze how to design and implement a student data collection application at Ma'had Tahfizhul Qur'an "Ahlus Shuffah" Balikpapan which can run on two different platforms, namely Detskop and Android. This research aims to produce an information system for managing student data and mobile-based student memorization data that runs on the Android platform and controlling student development and student memorization will become easier and more computable. The research method uses the waterfall method. The novelty of this research uses the design of a data collection application built using Android Studio and storing the data in an online database, which previously still used a manual system which was very troublesome, especially the invalidity and mismatch of data. The software used to build this application is Android Studio 3.1.2 using a database that can be operated online, namely Firebase. The results of this research make it easier to control the development of students' memorization and make it easier to check the data that has been input.